Distribusi Temporal dan Spatial Arthropoda Pada Berbagai Jenis Tumbuhan Liar di Agroekosistem - Muhammad Richsan Yamin; Siti Annisaa'ul Kariimah; Nadya Rizky Nuzul Ramadhanti; Intan Ayu Idha Wulandari (Fakultas MIPA UNM, 2021)
Abstract. The purpose of this research were to (1) analyse the temporal and spatial distribution of arthropods in the cassava and eggplant agroecosystem areas. (2) Analysing the temporal and spatial distribution of arthropods in the maize agroecosystem. This research was divided into 2 stations, the first station which is near the trail in the eggplant and corn agroecosystem, while for the second station on the corn agroecosystem, the two research locations are in Maccorawalie Village, Watang Sawitto District, Pinrang Regency, South Sulawesi. This research use the analytical method to analyse the observations and also identify the families of each arthropod found, then count the number of arthropods in each species and measure the diversity and abundance of each wild plant found at station 1 and station 2 in the morning and afternoon. The translation of the results obtained from the results of data collection at two stations in two data collection times (morning and afternoon) in the day, where the morning is 06.00-8.00 WITA Zone, while in the afternoon at 16.00-17.30 WITA zone. This is due to abiotic factors such as temperature and humidity, where the temperature in the morning is 23°C with 92% humidity, while the afternoon temperature is 25°C with 77% humidity. Arthropods have a different temporal distribution because this is related to the biological clock in each Arthropod. Biological clock allows Arthropods to determine when to work and rest. The existence of a rhythm in insects resulted in the division of two living groups, known as diurnal (active during the day) and nocturnal. Abiotic factors in the form of light intensity, temperature and humidity, affect the activity patterns of insects that have a certain temperature range, light intensity and humidity in Maccorawalie Village, Watang Sawitto District, Pinrang Regency.Keywords: temporal distribution, spatial distribution, arthropods, agroecosystem.